Asthenia as a pressing health issue FOR women with non-psychotic mental disorders: age perspective - M. F. Belokrylova; N. P. Garganeeva; V. B. Nikitina; E. M. Epanchintseva (Бюллетень сибирской медицины)
The aim of the study was to investigate the clinical phenomena of asthenia and subjective well-being of women aged 40–65 with non-psychotic mental disorders.Materials and methods. A complete examination of 204 women aged 40–65 who received treatment for non-psychotic mental disorders within 1 year has been conducted. The data on the clinical phenomena of asthenia were supplemented by patients’ rank assessment of fatigue and mood, determination of asthenia severity using the Multidimensional Fatigue Inventory (MFI-20), a calculation of the Kupperman menopausal index, and an assessment of the emotional component of well-being on the subjective well-being scale. For statistical processing, the methods of descriptive statistics and non-parametric statistics were used (for comparing independent samples – the Kruskal–Wallis criterion and Mann–Whitney U-criterion were applied; for identifying the connection of signs – Spearman rank correlation was used).Results. The profile of the identified disorders included neurotic, stress-related and somatoform disorders (F40-49) – 67.7%, organic non-psychotic disorders (F06.4; F06.6) – 27.0%, and affective disorders (F34.1) – 5.4%. The organic asthenic disorder was also the second most frequent diagnosis among 69 patients. 196 women complained of fatigue. Patients with complaints of constant fatigue weresignificantly more likely to report headache, irritability, low mood, pessimistic thoughts, drowsiness, and asthma attacks. Their low level of subjective well-being correlated with higher rates of asthenia on MFI-20 subscales, except for the “Reduced Motivation” subscale.The rates for all MFI-20 subscales among women with asthenic syndrome were lower than for patients with the depressive syndrome. A lower level of subjective well-being was revealed in patients with depressive, anxiety-depressive and anxiety-phobic syndromes, which differed by more pronounced manifestations of asthenia.Conclusion. The conjugation and complementarity of the scales used in the study made it possible to measure both asthenia and the emotional state and subjective well-being of women with non-psychotic mental disorders associated with it.